Contribuições e desafios da cadeia formativa no processo de formação continuada dos coordenadores pedagógicos da Rede Municipal de Ensino de São Paulo - Santos, Maria de Fátima Barbosa (2023)
This qualitative research focuses on the Training Chain of the public education system of São Paulo and its actions on the professional development of pedagogical coordinators, agents of the training chain who are responsible for teachers’ in-service continuous training, among other duties, and, therefore, must undergo constant improvement as a fundamental step for better training actions. Main objective was to investigate the Training Chain of the public education system of São Paulo as a continuous training process, through the eyes of experienced pedagogical coordinators (more than ten years at the job) and inexperienced ones (less than two years at the job). Specific objectives were: a) to understand if and how the institutional training offered by the public education system answers the pedagogical coordinators’ training needs for teacher training; b) to analyze the pedagogical coordinators’ perception on how the Training Chain influences their teacher training role and, consequently, the creation of training subjects; c) to bring notes that might contribute to the building of public policies directed to pedagogical coordinators’ continuous training. Data was produced through semi-structured interviews, and analysis was inspired by Prose Analysis. Results showed gaps on the Training Chain. Feedback process does not always work, leading to losses on pedagogical coordinators’ continuous training and on the constitution of their professional identities as teacher trainers. Data also showed self-study and the exchange of knowledge between experienced and inexperienced coordinators as common strategies when these professionals need support to build their training subjects. These results may contribute with the reflection about pedagogical coordinators’ training needs and with the creation of public policies that help them prepare for their work as teacher trainers